Transvenous Lead Extraction From Simple Traction to Internal Transjugular Approach - Bongiorni, Maria Grazia (Springer Milan : Imprint: Springer, 2011)
In recent years, indications for defibrillators and cardiac resynchronization therapy have expanded enormously. The implanted leads necessary for these devices to function, however, have a limited life span, and their extraction will be an increasing issue in clinical practice for treating short- and long-term complications, such as infections and lead failures. Aim of this book is to provide state-of-the-art techniques for lead extraction and to cover subjects such as lead characteristics, indications for lead removal, patient preparation, extraction tools and techniques, complication prevention and management. A series of tips and tricks for approaching particular conditions (tight costoclavicular space, fractured leads, implantable cardioverter-defibrillator leads, endangered leads) is presented. A new extraction technique through the internal jugular vein is described: several examples are given, and high-quality images help thoroughly depict this innovative procedure. An excellent resource for all individuals involved in managing cardiac patients: cardiologists, arrhythmologists, surgeons, general practitioners, pediatricians, and postgraduate students in those disciplines.